FUNGSI RPJMDes DALAM MENINGKATKAN PEMBANGUNAN DI DESA AYULA SELATAN KECAMATAN BULANGO SELATAN KABUPATEN BONE BOLANGO - Alkatiri, Ramlah; Umadji, Fatmawaty (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2023)
The Village Medium-Term Development Plan (RPJMDes) is a mandate of law number 25 of 2004 and law number 6 of 2014. This study aims to determine how the function of the Village Medium Term Development Plan (RPJMDes) in improving development in Ayula Selatan Village District South Bulango Bone Bolango Regency. This study uses a qualitative approach by using informants as sources to answer the research objectives. An understanding of the functions of the Village RPJM can be seen from 4 aspects that are used as benchmarks, namely a) planning, where planning has been carried out in accordance with the stages and mechanisms for preparing the Village RPJM b) organizing, where the village organizing system is already running according to the division the work and duties and functions of each person in charge c) directing (direction), and d) Coordinating where this aspect becomes the standard operating procedure (SOP) for the village government of South Ayula in monitoring the implementation of development programs. Based on these four indicators, the RPJMDes function has increased development in South Ayula Village as evidenced by the realization of the development program as stipulated in the RPJMDes of Ayula Selatan Village